Handbook of deposition technologies for films and coatings : science, applications and technology - Martin, Peter M. (Elsevier, 2010)
This 3e, edited by Peter M. Martin, PNNL 2005 Inventor of the Year, is an extensive update of the many improvements in deposition technologies, mechanisms, and applications. This long-awaited revision includes updated and new chapters on atomic layer deposition, cathodic arc deposition, sculpted thin films, polymer thin films and emerging technologies. Extensive material was added throughout the book, especially in the areas concerned with plasma-assisted vapor deposition processes and metallurgical coating applications. - Explains in depth the many recent improvements in depo.
Keywords: Coating processes.; elektronické knihy; electronic books